Nutritional Status and Health-Related Quality of Life in Men with Advanced Castrate-Resistant Prostate Cancer. (7th February 2022) - Cavka, Luka; Pohar Perme, Maja; Zakotnik, Branko; Rotovnik Kozjek, Nada; Seruga, Bostjan
Abstract: Background Despite professional recommendations malnutrition is not adequately addressed in cancer patients. Here, we explored whether nutritional status (NS) is associated with HRQoL in men with metastatic castrate-resistant prostate cancer (mCRPC). Methods: Men with mCRPC enrolled into this prospective observational study were allocated to one of the four NS categories based on clinical, laboratory, and patient self-reported criteria: well-nourished (WN), nutritional risk without criteria for cachexia/sarcopenia (NR), sarcopenia, and cachexia. The HRQoL was evaluated by the Functional Assessment of Cancer Therapy-Prostate (FACT-P) questionnaire. Association between NS and self-reported HRQoL was sought by the linear regression model, which was adjusted for known prognostic variables and body mass index. Results: Over the period of two years, 141 patients were enrolled. Their median age was 74.1 years (IQR 68.6–79.4 years) and majority of them were minimally symptomatic. Fifty-nine patients (41.8%) were WN, followed by 24 (17%), 42 (29.8%), and 16 (11.4%) patients with NR, sarcopenia, and cachexia, respectively. As compared to WN patients, all three other NS categories were significant negative predictors of HRQoL ( P  < 0.04). Conclusions: Abnormal NS is highly prevalent in men with mCRPC and is negatively associated with their HRQoL, which supports the recommendation for management of malnutrition in these patients.